Pedagogical Considerations between Teaching Fitness and in Higher Education - Rubin, Lisa M.; Stokowski, Sarah (Kentucky SHAPE, 2023)
The purpose of this essay is to explore synergy between the pedagogy of teaching group fitness classes and that of teaching in higher education (i.e., undergraduate and graduate courses). The authors are both faculty and group fitness instructors. Through a brief review of literature, personal experiences as group fitness instructors, and perspectives of other faculty who teach fitness, the essay sought to explore pedagogical considerations between teaching fitness and teaching in higher education. Instructional differences, similarities, and overlaps were considered. In addition, teaching training and pandemic pivoting were also explored. The authors concluded with a call for more scholarly discourse on teaching in group fitness and higher education.
Keywords: Pandemic; Instruction; Group Fitness; College Teaching; Higher Education; Group Fitness